The immunogenic profile and immunomodulatory function of mesenchymal stromal / stem cells in the presence of Ptychotis verticillata - Mehdi Najar; Fatima Bouhtit; Saida Rahmani; Abderrahim Bouali; Rahma Melki; Mustapha Najimi; Philippe Lewalle; Makram Merimi (Heliyon, 2024)
Mesenchymal stromal/stem cells (MSCs) are considered to be a promising immunotherapeutic tool due to their easy accessibility, culture expansion possibilities, safety profile, and immunomodulatory properties. Although several studies have demonstrated the therapeutic effects of MSCs, their efficacy needs to be improved while also preserving their safety. It has been suggested that cell homeostasis may be particularly sensitive to plant extracts. The impact of natural compounds on immunity is thus a fascinating and growing field. Ptychotis verticillata and its bioactive molecules, carvacrol and thymol, are potential candidates for improving MSC therapeutic effects. They can be used as immunotherapeutic agents to regulate MSC functions and behavior during immunomodulation. Depending on their concentrations and incubation time, these compounds strengthened the immunomodulatory functions of MSCs while maintaining their immune-evasive profile. Incubating MSCs with carvacrol and thymol does not alter their hypoimmunogenicity, as no induction of the allogeneic immune response was observed. MSCs also showed enhanced abilities to reduce the proliferation of activated T cells. Thus, MSCs are immunologically responsive to bioactive molecules derived from PV. The bioactivity may depend on the whole phyto-complex of the oil. These findings may contribute to the development of safe and efficient immunotherapeutic MSCs by using medicinal plant-derived active molecules.